ANALISIS NILAI PENDIDIKAN KARAKTER DALAM DONGENG KUPU-KUPU INDAH YANG SOMBONG KARYA YOGA TRIANA - Rouli Simanullang; Sitorus, William T; Widya Octavianty; Fitriani Lubis (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The purpose of this study was to examine educational values ​​in the form of quotations from the fairy tale "The Arrogant Beautiful Butterfly" by Yoga Triana. The method used in this research is qualitative. The analysis technique in this study is to analyze documents in the form of fairy tales. The object of this research is the educational values ​​in the fairy tale "The Beautiful Arrogant Butterfly" by Yoga Triana. With this the author collects data by reading from books and journals. The results of this research on fairy tales are that as a whole, these fairy tales already reflect the educational values ​​needed in fairy tales as a way of life or as a way for students to have good morals in socializing.